Minds Wide Shut : How the New Fundamentalisms Divide Us - Morson, Gary Saul, 1948-; Schapiro, Morton Owen (Book collections on Project MUSE., 2021)
"Gary Saul Morson, a literature scholar at Northwestern, and Morton Schapiro, an economist, and president of Northwestern, are authors of our book Cents and Sensibilities, on what economists, who tend to reduce reality to economic fundamentalist thinking, can do to correct and enhance their accounts of social life. In their new book, Morton and Schapiro extend their discussion to encompass not only the market fundamentalism of economics, but various other forms of intellectual fundamentalism from politics through religion through literature. In each case and overall, they emphasize the importance of cross-disciplinary dialogue in correcting the errors of these diferent academics fundamentalisms, while helping to construct richer accounts of culture and society"--